Contribution A La Caracterisation Diagraphique Des Depots Carbonates Du Cretace Du Bassin Sedimentaire De Cote D’ivoire - Cyrille, Yao Kouadio; Alfred, Kouassi Kouamé; Hervé, Boga Atabli; Sylvain, Monde; Bruno, Digbehi Zéli; Victor, N’da Loukou (European Scientific Journal, ESJ, 2016)
To know the petrophysical characteristics associated with sedimentary facies gammay ray logs providing information on the natural radioactivity of sedimentary rocks and the sonic logs which document on facies and petrophysical variations rocks were studied. This study focused on three (3) wells (BH-X, DH-X and MR-X) bored in the offshore basin of Abidjan margin (Côte d’Ivoire) for which the lithogy is constituted of clay alternating with sand an sandstone at the base surmounted by limestone and marls which are covered by clay series. It reveals that two deposits phases occurred during the carbonate sedimentation. Through the gamma ray logs, it appears that the clay phases have low radioactivity, which often progress to average values. This radioactivity recorded in clays would be linked to the low organic matter content and leaching reworked elements. In marl phases radioactivity is medium to high indicating a high content of uranium, thorium and potassium deriving from clay minerals. The gamma ray log varies significantly in limestone phases reflecting the heterogeneity of deposits. Strong radioactivity values in some limestone layers are related to their homogeneity and the present of organic matter. Fluctuations result from long-term changes in submarine hydrothermal flow and may indicate significant variations in facies (crystalline limestone, marl and clay). There are more or less dolomitised layers alternating with more homogeneous chemical limestone benches, biogenic limestone debris of organisms and past clay. The sonic log has two phases in the marl and limestone interval. In the marl phase, the acoustic wave velocity is almost constant, but in the limestone phase velocities fluctuate. Indeed, marl interval contains heterogeneous deposits. Generally the velocity is still low in impermeable and little porous clay. In marls, relatively high propagation velocity implies that they are less penetrable as clays because of the presence of fluid. The sonic log fluctuations in the limestone stage reflect the heterogeneity of deposits. Calcareous layers generally have a shorter time of wave propagation, suggesting that they are indurated, recrystallized and homogeneous. By against certain layers are poorly penetrable and show the presence of fluid. The limestone is fractured, so more porous than clay and marl. The porosity may be related to diagenesis after being dessoluted.